Advances in databases and information systems : 22nd European Conference, ADBIS 2018, Budapest, Hungary, September 2-5, 2018, Proceedings /: 22nd European Conference, ADBIS 2018, Budapest, Hungary, September 2-5, 2018, Proceedings. (2018) - Unknown
No abstract available